2020
DOI: 10.1002/jso.25880
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of segmentectomy vs lobectomy in pathologic stage IA (≤2 cm) invasive lung adenocarcinoma: A population‐based study

Abstract: Background and Objectives: For early-stage invasive lung adenocarcinoma, it remains unclear whether segmentectomy can yield outcomes equivalent to those of lobectomy. This study aimed to compare survival outcomes after segmentectomy and lobectomy among patients with stage IA invasive lung adenocarcinoma. Methods:We identified patients with stage IA (≤2 cm) invasive lung adenocarcinoma who underwent segmentectomy or lobectomy from the Surveillance, Epidemiology, and End Results database (2004)(2005)(2006)(2007)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“… 27 Similar studies had confirmed that wedge resection was inferior to lobectomy with mediastinal lymph node dissection in stage I adenocarcinoma. 28 Somewhat differently, a context had found that lobectomy and pulmonary segmentectomy were nearly identical in prognosis for patients with tumor size ≤ 3cm, while lobectomy had the prognostic superiority in patients with >3 and ≤4cm. 28 Therefore, which type of surgery should be adopted for stage I NSCLC required a further concrete analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 Similar studies had confirmed that wedge resection was inferior to lobectomy with mediastinal lymph node dissection in stage I adenocarcinoma. 28 Somewhat differently, a context had found that lobectomy and pulmonary segmentectomy were nearly identical in prognosis for patients with tumor size ≤ 3cm, while lobectomy had the prognostic superiority in patients with >3 and ≤4cm. 28 Therefore, which type of surgery should be adopted for stage I NSCLC required a further concrete analysis.…”
Section: Discussionmentioning
confidence: 99%
“…27 Similar studies had confirmed that wedge resection was inferior to lobectomy with mediastinal lymph node dissection in stage I adenocarcinoma. 28 Somewhat differently, a context had found that…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple investigations have shown that in the case of tumors less than 2 cm in size, a segmentectomy can lead to oncologically sufficient outcomes [ 21 , 22 , 23 , 24 ] and lung-cancer-specific survival [ 25 ] without any difference in perioperative mortality or morbidity [ 3 ]. As such, segmentectomy should be strongly considered in this population as outcomes are comparable to lobectomy.…”
Section: Surgical Indication By Stagementioning
confidence: 99%
“…Adjusted NRCs of segmentectomy or wedge vs. lobectomy in apparently healthy patients are shown in Table 1 (16,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), Table 2 (16,36,42,47,48,50,(53)(54)(55)(56)(57)(58)(59)(60)(61)(62), Table 3 (36,47,48,50,(63)(64)(65)(66) and Figures S2-1…”
Section: Survivalmentioning
confidence: 99%